2006
DOI: 10.1007/s00439-006-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations

Abstract: Isolated oral clefts, including cleft lip with/without cleft palate (CL/P) and cleft palate (CP), have a complex and heterogeneous etiology. Case-parent trios from three populations were used to study genes spanning chromosome 2, where single nucleotide polymorphic (SNP) markers were analyzed individually and as haplotypes. Case-parent trios from three populations (74 from Maryland, 64 from Singapore and 95 from Taiwan) were genotyped for 962 SNPs in 104 genes on chromosome 2, including two well-recognized can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
1
43
0
10
Order By: Relevance
“…The SNP rs142167 showed a highly significant association, while the SNP rs9890413 was also shown to be associated with NSCL/P. Beaty et al (2006) also showed the WNT6-WNT10A gene cluster to be associated with incidence of cleft lip and palate.…”
Section: Introductionmentioning
confidence: 86%
“…The SNP rs142167 showed a highly significant association, while the SNP rs9890413 was also shown to be associated with NSCL/P. Beaty et al (2006) also showed the WNT6-WNT10A gene cluster to be associated with incidence of cleft lip and palate.…”
Section: Introductionmentioning
confidence: 86%
“…Here, the focus is on nonsyndromic CLP which accounts for approximately 70% of all cases with CLP and 50% of cases with isolated cleft palate [14]. Syndromic forms can be subclassified into Mendelian disorders, chromosomal syndromes and uncategorised syndromes [15].…”
mentioning
confidence: 99%
“…ZNF533 has been identified as a putative repressor of transcription. It is widely expressed in adult brain tissues and is involved in the development of the palate and lip (Beaty et al, 2006). Several studies have shown that deletions of the ZNF533 gene are associated with mental retardation (Kleefstra et al, 2004;Monfort et al, 2008).…”
Section: Discussionmentioning
confidence: 99%